BRAIN–COMPUTER INTERFACES IN NEUROLOGICAL REHABILITATION: TECHNOLOGICAL INNOVATIONS, NEURAL DECODING STRATEGIES, AND CLINICAL TRANSLATION CHALLENGES IN MODERN NEUROREHABILITATION (Global Conference on Medical and Health Sciences, 2026)
Brain–computer interfaces (BCIs) have emerged as a transformative technology in neurological rehabilitation, enabling direct communication between the brain and external devices to restore lost motor and cognitive functions. Advances in neural signal acquisition, decoding algorithms, and neurofeedback systems have significantly improved the performance and clinical applicability of BCIs. These systems are increasingly being utilized in patients with neurological impairments, including Stroke, spinal cord injury, and neurodegenerative disorders, where conventional rehabilitation approaches often have limited effectiveness.
Keywords: Brain–computer interface; Neurorehabilitation; Neural decoding; EEG; Neuroplasticity; Assistive technology; Stroke recovery; Machine learning